Morphological and mechanical alterations in articular cartilage and subchondral bone during spontaneous hip osteoarthritis in guinea pigs - Gao, Jiazi; Ren, Pengling; Gong, He (Frontiers in Bioengineering and Biotechnology, 2023)
Objectives: This study aimed to investigate the morphological and mechanical changes in articular cartilage and subchondral bone during spontaneous hip osteoarthritis in guinea pigs. Materials and methods: Hip joints of guinea pigs were investigated at 1, 3, 6, and 9 months of age (hereafter denoted as 1 M, 3 M, 6 M, and 9 M, respectively; n = 7 in each group). Morphological and mechanical alterations during spontaneous hip osteoarthritis in guinea pigs were investigated. The alterations included the micromechanical properties of articular cartilage (stiffness and creep deformation), microstructure of the subchondral bone (bone mineral density, bone volume fraction, trabecular thickness, trabecular number, and trabecular separation), micromorphology of the articular cartilage, and surface nanostructure (grain size and roughness) of the articular cartilage and subchondral bone. Results: Micromechanical properties of articular cartilage in 1 M showed the lowest stiffness and highest creep deformation with no significant differences in stiffness or creep deformation amongst 3 M, 6 M, and 9 M. Articular cartilage thickness decreased with age. The earliest degeneration of articular cartilage occurred at 6 months of age, characterised by surface unevenness and evident chondrocytes reduction in micromorphology, as well as increased grain size and decreased roughness in nanostructure. No degeneration at micro- or nanostructure of subchondral bone was observed before 9 months. Conclusions: Morphological degeneration of cartilage occurred before degeneration of mechanical properties. Meanwhile, degeneration of cartilage occurred before degeneration of subchondral bone during hip osteoarthritis. The current study provided novel insights into the structural and micromechanical interaction of hip osteoarthritis, which can serve as a theoretical basis for understanding the formation and progression of osteoarthritis.